Phylogeography, more than elevation, accounts for sex chromosome differentiation in Swiss populations of the common frog (Rana temporaria). (5th December 2019) - Phillips, Barret C.; Rodrigues, Nicolas; Jansen van Rensburg, Alexandra; Perrin, Nicolas
Abstract: Sex chromosomes in vertebrates range from highly heteromorphic (as in most birds and mammals) to strictly homomorphic (as in many fishes, amphibians, and nonavian reptiles). Reasons for these contrasted evolutionary trajectories remain unclear, but species such as common frogs with polymorphism in the extent of sex chromosome differentiation may potentially deliver important clues. By investigating 92 common frog populations from a wide range of elevations throughout Switzerland, we show that sex chromosome differentiation strongly correlates with alleles at the candidate sex‐determining gene Dmrt1 . Y‐specific Dmrt1 haplotypes cluster into two main haplogroups, YA and YB, with a phylogeographic signal that parallels mtDNA haplotypes: YA populations, with mostly well‐differentiated sex chromosomes, occur primarily south of the main alpine ridge that bisects Switzerland, whereas YB populations, with mostly undifferentiated (proto‐)sex chromosomes, occur north of this ridge. Elevation has only a marginal effect, opposing previous suggestions of a major role for climate on sex chromosome differentiation. The Y‐haplotype effect might result from differences in the penetrance of alleles at the sex‐determining locus (such that sex reversal and ensuing X‐Y recombination are more frequent in YB populations), and/or fixation of an inversion on YA (as supported by the empirical observation that YA haplotypes might not recombine in XYA females).